The comparison of the effect of static and dynamic exercise on heart rate variability in elite sportsmen - Tacoy, G.; Yazc, G.; Eroglu, H.; Turfan, M.; Okyay, K.; Ozdemir, M.; Cengel, A. (Journal of Electrocardiology, 2007)
Sixteen football players (mean age, 22.6 years) and 14 weight lifters (mean age, 23.1 years) who were highly trained elite sportsmen in the School of Physical Education and Sport of Gazi University and who have been participating in national and international competitions were enrolled in this study. To exclude the gender differences, all individuals were men. Subjects had no personal history of any major medical condition, and none of them were taking any medication. All participants underwent a basal 24-hour Holter recording to assess the time-domain HRV parameters (SDNN, SDANN, RMMSD, pNN50, TI). All measurements were performed in accordance with the Task Force of The European Society of Cardiology and The North American Society of Pacing and Electrophysiology.